MENINGKATKAN KEPUTUSAN PEMBELIAN MELALUI ELECTRONIC WORD OF MOUTH DI BAKSO LAPANGAN TEMBAK SENAYAN - Martin Cokretes; Parlagutan Silitonga (LPPM Universitas Asa Indonesia, 2023)
This study aims to analyze the effect of product quality and restaurant atmosphere on purchasing decisions by mediating electronic word of mouth at Bakso Field Shoot Senayan. The population in this study were all customers at Bakso Lapangan Tembak senayan and the sampling technique used accidental sampling with 173 respondents. Methods of data collection using questionnaires distributed to respondents. The analysis used is SmartPLS 3.0. The results show that partially, there is an effect of product quality on electronic word of mouth, there is an effect of product quality on purchase decisions, there is an indirect effect of product quality through electronic word of mouth on purchase decisions, there is an influence of restaurant atmosphere on electronic word of mouth, there is the indirect effect of the restaurant atmosphere through electronic word of mouth on purchase decision, there is an influence of electronic word of mouth on purchase decision, while the restaurant atmosphere hypothesis on purchase decision shows no effect.